An Armijo-type method for pseudomonotone equilibrium problems and its applications - Anh, P. N.; Le Thi, H. A. (Journal of global optimization, 2013)
We present a new algorithm for solving equilibrium problems, where the underlying bifunctions are pseudomonotone and not necessarily Lipschitz-type continuous. The algorithm is based on the auxiliary problem principle and the Armijo-type linesearch techniques. Convergence properties of the algorithms are established, among them the global convergence is proved under few assumptions. Applications to generalized variational inequalities and some numerical results are reported.